Longitudinal change in arterial stiffness after delivery in women with preeclampsia and normotension: a prospective cohort study - Sehun KIM (BMC Pregnancy and Childbirth, 2020)
Abstract Background Preeclampsia is associated with increased arterial stiffness during pregnancy. However, data on the longitudinal change in arterial stiffness after delivery in women with preeclampsia are lacking. In this pilot study, we aimed to examine the longitudinal change in arterial stiffness using the cardio-ankle vascular index after delivery in women with preeclamptic and normotensive pregnancies. Methods We enrolled pregnant women with preeclampsia (n = 37) and normotension (n = 36) who gave birth at Seoul National University Bundang Hospital between March 2013 and May 2016, and followed-up at day 1, 6 months, and 12 months after delivery. The longitudinal change in the cardio-ankle vascular index and other variables (blood pressure, lipid profiles, serum creatinine, and liver enzymes) were compared between the two groups using the mixed-effects model, and interactions among the main predictors were examined. Results The longitudinal change in the cardio-ankle vascular index did not significantly differ between the two groups (β = 0.11, 95% CI: − 0.31–0.54, p = 0.60). Predictors of the longitudinal change in the cardio-ankle vascular index included age, time since delivery, body mass index, and diabetes mellitus. Women with preeclampsia showed significantly elevated blood pressure, lipid profiles, serum creatinine, and liver enzymes compared to women with normotension over the course of 1 year of follow-up. Conclusions Preeclampsia is associated with unfavorable blood pressure and metabolic indices after delivery. However, we found no difference in the longitudinal change in arterial stiffness between women with preeclampsia and normotension over the course of 1 year after delivery. Trial registration Retrospectively registered at ClinicalTrials.gov on October 29, 2019 ( NCT04142268 ).